Arrival [videorecording (DVD)] - Adams, Amy; Renner, Jeremy; Whitaker, Forest; Chiang, Ted (Paramount Pictures, 2017)
When mysterious spacecraft touch down around the world, a team, including linguist Louise Banks, is brought together to investigate. As mankind teeters on the verge of global war, Banks and the team race against time for answers, and to find them, she will take a chance that could threaten her life, and quite possibly humanity.